Upaya Hukum Penyelesaian Sengketa Nasabah Terhadap Bank Yang Mengalami Perubahan Sistem Operasional Perbankan - Lolo, Theresia Fedora (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2020)
Abstract – Economic development continuing forward led to an increase the need for credit .There are a special institution financial services services provided by storage and distribution community funds at once called bank. The distribution of funds listed in credit agreement based on article 1338 BW. The problems that emerged were loans become non-performing because borrowers were unable to settle credits. In general , if there is dispute in the field of banking resolved through the litigation and the non-litigation. The problems in this research was about the legal remedy that can be conducted by customers of the bank who changed banking operational system. This research adopting juridical normative. Material used covering material law primary and secondary legal entity. Based on the research and discussion, concluded that customers should seek solution through the non-litigation first before in litigation through the courts in the role of OJK in dispute resolution. Based on conclusions, so it is suggested that OJK set Standart of Operational at an institute of financial services to attach / inform dispute resolution procedures as a form of consumer protection in financial services sector. Keywords: Legal remedy, dispute resolution, Bank